Testing procedures and guidelines for flexural stresses during lifting of full-scale, tilt-up panel instrumentation in the field - Benton, Katherine Marie (Kansas State University, 2020)
According to the Tilt-Up Concrete Association, over 10,000 buildings, which enclose more than 650 million square feet, are constructed each year using the tilt-up concrete construction method. This construction method is economical when done correctly. Panel lifting is proprietary and independently tested. Typically, the panel lifting inserts are designed for the highest tension forces, which occur when the panel is initially lifted from horizontal due to the initial suction forces to release the panel from the slab, where the failure of the lift insert would be tension and the concrete surrounding the insert would be punching shear. Lift inserts are also designed for the highest shear forces, which occur when the panels are set in their final vertical position prior to the crane rigging being removed, due to the inserts supporting the panels until they are properly braced and released. A scaled test has been conducted to determine the locations of maximum compressive and tensile strains (Abi-Nader, 2009). However, little to no published research exists on the actual behavior of full-size tilt-up panels during lifting. This report outlines the steps and procedures to conduct full-scale testing of panels in order to have a more comprehensive understanding of tilt-up panel flexural behavior during erection.
Keywords: Tilt-up; Instrumentation; Field testing; Strain gauge; Wireless testing